1996
DOI: 10.1006/dbio.1996.0020
|View full text |Cite
|
Sign up to set email alerts
|

orthodenticleIs Required for Photoreceptor Cell Development in theDrosophilaEye

Abstract: Drosophila photoreceptor cells (R cells) develop from the eye imaginal during the third instar larval stage and acquire their adult morphology during pupation. We show that orthodenticle (otd), a homeobox gene, is required for R-cell morphogenesis during pupation. otdUV-insensitive (otduvi) is a hypomorphic allele of otd that only affects R-cell development. The R-cell rhabdomeres are disorganized in otduvi, and there is a disruption of proximal-distal development in the eye. The otd genomic structure was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 0 publications
7
112
0
Order By: Relevance
“…First, the rhabdomere defects observed otd uvi and Pph13 hazy mutants are similar (Vandendries et al, 1996). In each case, the defects appear not to be the result of degeneration but a failure in their biogenesis.…”
Section: Pph13 Is Only Required For Photoreceptor Terminal Differentimentioning
confidence: 90%
See 1 more Smart Citation
“…First, the rhabdomere defects observed otd uvi and Pph13 hazy mutants are similar (Vandendries et al, 1996). In each case, the defects appear not to be the result of degeneration but a failure in their biogenesis.…”
Section: Pph13 Is Only Required For Photoreceptor Terminal Differentimentioning
confidence: 90%
“…Previous reports have established or implicated eyeless (Pax6), orthodenticle (otd) and Onecut homeodomain genes in eye development (Nguyen et al, 2000;Quiring et al, 1994;Vandendries et al, 1996). What is the relationship between these various homeodomain transcription factors and how do they coordinate photoreceptor terminal differentiation?…”
Section: Pph13 Is Only Required For Photoreceptor Terminal Differentimentioning
confidence: 99%
“…Subsequent studies showed that Otd plays an essential role in Drosophila photoreceptor development (Vandendries et al, 1996) by regulating the expression of opsin genes (Tahayato et al, 2003). Mammals have three Otd orthologs, Otx1, Otx2 and Crx, which is equivalent to Otx5 in fish, amphibians and chick (Plouhinec et al, 2003).…”
Section: Factors Specifying the Photoreceptor Lineage -Otx2 And Crxmentioning
confidence: 99%
“…Otd expression begins at the end of PR recruitment and is expressed in all PRs throughout development (Vandendries et al, 1996). (E-G) Larval (E), 50% pupal (F) and adult (G) eye co-staining with Otd (purple) and Sens (green).…”
Section: Research Articlementioning
confidence: 99%